Biosynthesis, characterization and photo-catalytic degradation of methylene blue using silver nanoparticles. (2020) - Ahmad, Tokeer; Veenu,; Nazim, Arsalan; Farooq, Umar; Khan, Huma; Jain, Sapan K.; Ubaidullah, Mohd.; Ahmed, Jahangeer
Abstract: Silver Nanoparticles have been successfully synthesized using Milletia pegunesis leaf extract at room temperature. X-ray diffraction studies (XRD) attributed to the formation of highly crystalline cubic silver nanoparticles. Transmission electron microscopic (TEM) studies showed the distribution of particles of silver in the range of 60–90 nm with an average particle size of 80 nm. Dynamic light scattering (DLS) measurement shows that the particle size ranges from 50–150 nm for Ag nanoparticles. Surface area measurements give the specific surface area of 26.7 m 2 g −1 . UV–Visible absorption spectrum of silver nanoparticles shows surface plasmon resonance band at 430 nm. FT-IR shows the appearance of band at 1623 cm −1 which may be attributed to amide linkage and the stretching band at 3280 cm −1 is due to alcoholic and phenolic linkages present in biomolecules of Milletia pegunesis . The degradation rate of methylene blue dye in presence of silver nanoparticles under sun light was found to increase with the increase in reaction time.